PENGARUH TAYANGAN FILM RELIGI TERHADAP AKHLAK SISWA: STUDI DI SMK NEGERI CIKARANG BARAT - Al-Adawiyah, Robi?ah; Lubis, Rabiyanur (Turats, 2015)
Impressions flourishing religious film that is both entertaining as well in addition to providing moral values are positive. Because the stories shown that about how religious people in the act, behave and speak the word, both in the human relationship with God, parents, relatives, friends, neighbors, even to animals, plants, and inanimate objects. The problems of this study is, "Is there any film footage of Religious Influence on Morals Students in Vocational High School 1 North Cikarang". Testing research results significant to the r value of 0.56 at ? = 0.05 was obtained with T_tabel T_hitung = 5.22 = 1.67 then significant or large donations 31.36% means that there are other factors that influence amounted to 68.64% , Thus there are positive influence between religious film impressions of the morals of students in SMK Negeri 1 Cikarang Barat.